(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This scientific article systematically and theoretically analyzes the formation of the concept of “New Uzbekistan” in the science of religious studies, its interaction with modern religious views, and its impact on the transformation of religious thought. The focus of the research is on the issues of a new model of state-religion relations, the reinterpretation of the principles of religious tolerance, freedom of conscience, and secularism, as well as the role of religious consciousness in the modernization process. The article interprets the idea of “New Uzbekistan” not only as a political and legal program, but also as a complex cultural and philosophical phenomenon that directly affects the evolution of religious consciousness and social thought. The complex relationships between historical and religious heritage, global religious processes, and national values in the formation of modern religious views are revealed, and their scientific explanation is given based on the methodological capabilities of the science of religious studies. The results of the study substantiate the need to integrate the science of religion with modern social processes and show the priority of a scientific-enlightenment approach to the radicalization of religious views.